Improvement of filter paper packinf defects using lean and six sigma approaches - Muhammad Amar Hakim Abd Wahab (School of Manufacturing Engineering, University Malaysia Perlis, 2016)
The black dot defect is a condition where coffee powder melt on filter paper while producing coffee sachet. This study was conducted in order to reduce black dot defect in producing coffee sachetby using Continuous Improvement Process (CIP) at the small medium enterprise (SME) food industry.